2014
DOI: 10.2527/jas.2014-8038
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Evaluation of a real-time wireless pH measurement system relative to intraruminal differences of digesta in dairy cattle1,2

Abstract: The aim of this study was to evaluate the accuracy and precision of indwelled wireless sensors relative to intrareticuloruminal differences in dairy cows transitioned from a forage to a high-concentrate diet. A feeding trial was performed with 8 rumen-cannulated Holstein cows. The cows were stepwise switched from 0 to 60% concentrate in the diet and fed 5 wk. Samples from the free ruminal liquid (FRL) from the ventral rumen and from the particle-associated ruminal liquid (PARL) in the rumen mat were manually t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 10 publications
2
38
0
1
Order By: Relevance
“…One concern of the indwelling sensors is that they provide data of pH only in the site they are located, namely in the reticulum as they are located in the reticulum within 24 h after administration (Gasteiner et al, 2009). The sensors used in this study were recently evaluated and have shown to satisfactorily reflect the pH of the free rumen liquid (Klevenhusen et al, 2014). Thus, the term reticuloruminal pH is used here.…”
Section: Reticuloruminal Ph and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…One concern of the indwelling sensors is that they provide data of pH only in the site they are located, namely in the reticulum as they are located in the reticulum within 24 h after administration (Gasteiner et al, 2009). The sensors used in this study were recently evaluated and have shown to satisfactorily reflect the pH of the free rumen liquid (Klevenhusen et al, 2014). Thus, the term reticuloruminal pH is used here.…”
Section: Reticuloruminal Ph and Temperaturementioning
confidence: 99%
“…Because this disorder lacks overt clinical signs, its diagnosis relies mostly on ruminal pH measurements; however, single-point measurements of rumen pH are not reliable for predicting the Long-term reticuloruminal pH dynamics and markers of liver health in earlylactating cows of various parities fed diets differing in grain processing E. Humer,* 1 A. Khol-Parisini,* 1 L. Gruber, † J. Gasteiner, † Sh. M. Abdel-Raheem,* 2 and Q. Zebeli* 3 risk of SARA compared with measuring the duration of pH below certain SARA thresholds (Penner et al, 2007), which can be obtained by continuous monitoring of rumen pH (Penner et al, 2007;Klevenhusen et al, 2014). Subacute ruminal acidosis is a prevalent metabolic disorder of cattle, and metabolic stress associated with SARA primarily afflicts the energy and lipid metabolism in different body tissues, most importantly in the liver and the mammary gland (Bionaz et al, 2007;Zebeli and Ametaj, 2009;Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Reticuloruminal pH and temperature were measured continuously throughout the experiment using wireless bolus sensors (Smaxtec Animal Care Sales GmbH, Graz, Austria). By using an applicator, these validated bolus sensors (Klevenhusen et al, 2014) were manually administered via the esophagus into the reticulorumen. Prior to their use, the boli were calibrated using a buffer solution at pH 7.0 following the company instructions and were registered to the computer software device afterward.…”
Section: Reticuloruminal Ph and Temperature And Monitoring Of Sara Comentioning
confidence: 99%
“…These wireless pH-transmitting units (3.5 cm i.d., 12 cm long and weighing 210 g), validated previously (Klevenhusen et al, 2014), were manually inserted into the reticulorumen via the esophagus on day 17 postpartum (Humer et al, 2015b). Before their use, the units were calibrated by a two-point calibration using a buffer of pH 4.0 and one of pH 7.0 following the company's instruction protocol.…”
Section: Reticuloruminal Phmentioning
confidence: 99%